RETHINKING CHILD CUSTODY (HADANAH) IN MODERN MUSLIM FAMILIES: BETWEEN MATERNAL PREFERENCE AND CHILD-CENTERED JUSTICE - Muhammad Zahid Abdullah Zuhri; Ainul Yakin; Muhammad Haris Miftah Sibawayhie (Universitas Nurul Jadid, 2026)
This study reexamines the concept of Hadanah in Islamic family law by highlighting the dominance of maternal preference amid changes in the structure of contemporary Muslim families. The study employs a normative-interdisciplinary approach that combines an analysis of classical fiqh, attachment theory in developmental psychology, and the framework of maqāṣid al-sharī‘ah. The findings indicate that the primacy of the mother in child-rearing reflects a socio-historical construction rather than an absolute normative principle. Modern psychological studies confirm that the quality of emotional bonds and the stability of care play a more decisive role than the caregiver’s gender identity. Meanwhile, the maqāṣid approach opens up a more flexible space for reinterpretation by prioritizing the child’s best interests as the primary orientation. This study offers a conceptual formulation of Hadanah based on child-centered justice, which places the child’s best interests as the primary basis for determining custody. This model is expected to enrich the discourse on Islamic family law reform, making it more responsive, contextual, and oriented toward substantive justice.